2007
DOI: 10.1063/1.2724911
|View full text |Cite
|
Sign up to set email alerts
|

Element-specific spin and orbital momentum dynamics of Fe∕Gd multilayers

Abstract: The role of orbital magnetism in the laser-induced demagnetization of Fe/Gd multilayers was investigated using time-resolved X-ray magnetic circular dichroism at 2-ps time resolution given by an xray streak camera. An ultrafast transfer of angular momentum from the spin via the orbital momentum to the lattice was observed which was characterized by rapidly thermalizing spin and orbital momenta. Strong interlayer exchange coupling between Fe and Gd led to a simultaneous demagnetization of both layers.1 Author t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 16 publications
(28 reference statements)
5
32
0
Order By: Relevance
“…Recently, Bartelt et al reported on an element-specific magnetization dynamics in Fe=Gd multilayers using x-ray magnetic circular dichroism (MCD). Interestingly, an almost simultaneous demagnetization is observed probing the Fe valence and Gd 4f shell, which could occur, e.g., due to hybridization of both constituents or the intense excitation by F abs 20 mJ=cm 2 [19].…”
mentioning
confidence: 99%
“…Recently, Bartelt et al reported on an element-specific magnetization dynamics in Fe=Gd multilayers using x-ray magnetic circular dichroism (MCD). Interestingly, an almost simultaneous demagnetization is observed probing the Fe valence and Gd 4f shell, which could occur, e.g., due to hybridization of both constituents or the intense excitation by F abs 20 mJ=cm 2 [19].…”
mentioning
confidence: 99%
“…An interesting ferrimagnetic system for this study is the family of amorphous rare-earth (RE)-transition-metal (TM) alloys, such as GdFeCo, for which the compensation points can be tuned in a wide temperature range by simply varying its composition [20]. However, due to the localized character of the spins responsible for magnetism in the RE ferrimagnetic sublattice, it is not clear whether its magnetization can be changed by laser pulses on a fs time scale [21].…”
mentioning
confidence: 99%
“…The interaction of a subpicosecond optical laser pulse with spins in a magnetic system has become a rapidly growing area of science [1][2][3][4][5][6][7][8][9][10][11] since the pioneering work by Beaurepaire et al Using a 60 fs optical laser pulse, they demonstrated an ultrafast (within about 1 ps) demagnetization in a Ni thin film. 1 After this observation, research on laser-induced demagnetization has been conducted at large in ferromagnetic transition metals (TMs) (e.g., Co, Ni), rare-earth (RE) metals (e.g., Gd, Tb), and their alloys (see Ref.…”
mentioning
confidence: 99%